2013
DOI: 10.1155/2013/486050
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surfactants on the Characteristics of Nickel Matrix Nanocomposite Coatings

Abstract: Nickel-based nanocomposite coatings were prepared from a Watts-type electrolyte containing reinforcement's particles (silicon carbide and graphite) to deposit onto the steel St-37 substrate. e electrochemical plating of the coatings in absence and presence of surfactants and reinforcements particles was carried out to optimize high quality coatings with appropriate mechanical and morphological features. e surfactants such as cetyltrimethylammonium bromide (CTAB), sodyumdodecyl sulfate (SDS), and saccharine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Introduction of surfactants in nano-suspensions is found to optimize the mechanical and morphological qualities of the final product. [14][15][16] In the current work, it is observed that the rate of buckling is completely altered by increasing the concentration of the surfactant (SDS, 0.2%-2% by weight) and is completely arrested above a critical value (>1% by weight). Addition of salt (AHC) in the dispersion causes re-initiation of buckling in the droplets.…”
Section: Introductionmentioning
confidence: 61%
“…Introduction of surfactants in nano-suspensions is found to optimize the mechanical and morphological qualities of the final product. [14][15][16] In the current work, it is observed that the rate of buckling is completely altered by increasing the concentration of the surfactant (SDS, 0.2%-2% by weight) and is completely arrested above a critical value (>1% by weight). Addition of salt (AHC) in the dispersion causes re-initiation of buckling in the droplets.…”
Section: Introductionmentioning
confidence: 61%
“…Coating performance can be developed by the addition of the surfactants like (cetyltrimethylammonium bromide (CTAB), sodyumdodecyl sulfate (SDS), and saccharine [20]. The advantage of adding surfactants is their dispersing effect of particles.…”
Section: Surfactant Addition / Typementioning
confidence: 99%
“…The electroplating parameters must be controlled during electrodeposition since they have significant effect on the coating properties, deposition efficiency and hydrogen evolution. Besides the current density, pH of the bath, bath temperature that places among the main electroplating parameters [36], there are more parameters including the type, the size, the concentration of the particles [37] and the addition of surfactants and their types [20]. The main properties of the coating can be listed as the corrosion resistance in TiO 2 -nickel coating [38], tribological properties in MoS 2 -nickel coating [4], mechanical properties in TiO 2 -nickel coating [38], internal stress in MoS 2 -nickel coating [9], texture in chromium -carbon deposit [39], particle content of the deposit [24] are severely affected by the electroplating parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Also, SLS is an anionic surfactant used as a wetting reagent or a brightener for Ni plating. On the other hand, SLS was studied as a stimulator for Ni composite plating [10,[15][16][17][18][19][20][21]. …”
Section: Introductionmentioning
confidence: 99%